Analysis of the production environment of a company producing rubber materials (Research, Society and Development, 2021)
In this article, the productive and organizational processes of a medium-sized company, focused on the manufacture and trade of rubber products, located in the Northwest region of Rio Grande do Sul are analyzed. CL Borrachas acts providing its customers with a diversified line agricultural parts such as hoses, compaction bands and technical parts, all manufactured using rubber waste. The objective was to analyze the processes developed within an organization and make suggestions for improvements in the production sector. To this end, methodologically, in addition to a bibliographic research, which served to add theoretical knowledge to the proposal for improvements to the company's production sector, on-the-spot verification studies were carried out, using 40 hours of observation. As a result, the study showed that the manufacturing method presented by the company can be improved. Therefore, investments are needed to improve and automate this method.